BLENDED LEARNING AND ITS TYPES - Djabborova Sh.B.; Amirova Umida Abdurazoq qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article provides an in-depth analysis of blended learning and its various types, offering insights into how this instructional model can enhance the learning experience. Blended learning combines traditional face-to-face instruction with digital tools to create a flexible and interactive learning environment. The article explores the different types of blended learning, their benefits, challenges, and successful implementation in educational settings. By examining real-world examples and best practices, the article aims to equip educators and learners with a comprehensive understanding of blended learning and its potential to transform education.